2020
DOI: 10.3389/fphy.2020.00105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Ultra-Low-Field MRI for in-vivo 3D Current Density Imaging of the Human Head

Abstract: Magnetic fields associated with currents flowing in tissue can be measured non-invasively by means of zero-field-encoded ultra-low-field magnetic resonance imaging (ULF MRI) enabling current-density imaging (CDI) and possibly conductivity mapping of human head tissues. Since currents applied to a human are limited by safety regulations and only a small fraction of the current passes through the relatively highly-resistive skull, a sufficient signal-to-noise ratio (SNR) may be difficult to obtain when using thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Several studies [8], [14] have indicated that low-eld MRI scanners have a low signal-to-noise ratio (SNR), resulting in noisy images. This was supported by Hömmen et al [10] that found out that image artifacts in uence the reconstruction quality.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Several studies [8], [14] have indicated that low-eld MRI scanners have a low signal-to-noise ratio (SNR), resulting in noisy images. This was supported by Hömmen et al [10] that found out that image artifacts in uence the reconstruction quality.…”
Section: Introductionmentioning
confidence: 59%
“…In developing countries, low-eld MRI equipment can provide an economical, long-term, and safe imaging option to high-eld MRI and computed tomography (CT) for brain imaging [8]. Moreover, Hömmen et al [10] revealed that existing ultra low-eld MRI systems can produce a su cient signal-to-noise ratio (SNR) required for clinical imaging. Huang et al [11] revealed that portable low-cost MRI systems can provide a point of care and timely MRI diagnosis especially to low-income countries where there are less than 0.1 MRI scans per 1,000,000 people [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…Technologies such as transcranial electric stimulation (TES), transcranial current density imaging (CDI) and neuronal source imaging based on electroencephalography (EEG) and magnetoencephalography (MEG), require methodologies for veri cation and validation. The assessment of new measurement and analysis chains can be pursued; applying (i) computational modeling and simulation [1] and (ii) metrological inspections [2,3]. While computational modeling and simulations provide a convenient way of assessing the above technologies, only metrological inspections allow the inclusion of real-world environmental in uences and can provide validation for computational modeling and simulations based on ground truth.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies such as transcranial electric stimulation (TES), transcranial current density imaging (CDI), and neuronal source imaging based on electroencephalography (EEG) and magnetoencephalography (MEG), require methodologies for veri cation and validation. The evaluation of new measurement and analysis chains can be addressed by (i) computational modeling and simulation [1] and (ii) metrological inspections [2,3]. While computational modeling and simulations provide a convenient way of assessing the above technologies, only metrological inspections allow the inclusion of real-world environmental in uences and provide the validation for computational modeling and simulations based on ground truth.…”
Section: Introductionmentioning
confidence: 99%